Exploring the use of a carcass detection dog to assess mowing mortality in Hungary - Deák, Gábor; Katona, Krisztián; Biró, Zsolt (Journal of Vertebrate Biology)
The intensification of agriculture has resulted in changes to mowing techniques. Slow manual cutting gave wild animals time to move to safer habitat patches and left hiding places for them. With the arrival of much faster mowing machinery this is no longer the case. To date, there are few ways of measuring direct mortality of new mowing capabilities on wildlife. In our study we aimed to answer whether a search dog, previously trained to find carcasses, could be used to assess mowing mortality of various species in different vegetation types in Hungary. Working with a handler, a carcass-trained dog fitted with a GPS surveyed several habitats post-mowing. All the animal remains detected were identified and recorded. 149 killed individuals were detected on 12 land parcels studied (158.2 carcasses/100 ha). The most affected vertebrate group was the reptiles (57%), all with protected status in Hungary, followed by mammals (30%) and birds (6%). Reptiles were predominantly represented by lizards, while rodents were the most common mammals found (91% and 70%, respectively). The dog also found dead brown hares, pheasants and roe deer (11% of all carcasses), which has implications for local wildlife managers. There was no statistical difference in the density of dead individuals between grassy meadows and leguminous vegetation, or in those found in the morning or afternoon. The mortality rate was not associated with the area of the mowed field. Our findings suggest that this is a viable use of carcass detection dogs. We recommend additional work of this kind to reveal the fatal impacts of new, faster mowing practices on wildlife living in agricultural landscapes to help mitigate conservation and game management conflicts.